EX-ANTE DEFERENCE AND REPARATIONS, THE CASE STUDIES OF COLOMBIA AND MEXICO - DOI 10.5935/2448-0517.20200035 - Garcia, Adriana Garcia (Juris Poiesis - Qualis A3, 2020)
Usually analyses of deference consider courts" review of past agency action. Governments interpret in a specific manner a norm or regulation and the judge decides the lawfulness of that interpretation after the fact. However, judges analyze governments" future decisions as well, for example in granting reparations for human rights violations. Such decisions generally engage in an analysis of future actions that the government should perform in order to redeem victims and guarantee the violation will not recur. The underpinning principle of judicial deference is that a court should not attempt to second guess or substitute its judgment for the judgment of another decision maker, nor should it opine on the wisdom of a policy or law. With respect to human rights violations, a more deferential approach might let the government determine what measures it will take by way of reparations and prevention of recurrence, while a non-deferential approach would spell out such measures in detail. Examining cases in Colombia and Mexico issued during the past 10 years, in this paper I argue that domestic courts have been granting reparations in a less deferential manner over time. This trend is very clear when analyzing non-repetition measures granted in these countries which include attempts to oblige governments to issue laws, reduce sanctions, and prohibit the transit of specific streets.